2017
DOI: 10.1515/eng-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Regression Models and Fuzzy Logic Prediction of TBM Penetration Rate

Abstract: This paper presents statistical analyses of rock engineering properties and the measured penetration rate of tunnel boring machine (TBM) based on the data of an actual project. The aim of this study is to analyze the influence of rock engineering properties including uniaxial compressive strength (UCS), Brazilian tensile strength (BTS), rock brittleness index (BI), the distance between planes of weakness (DPW), and the alpha angle (Alpha) between the tunnel axis and the planes of weakness on the TBM rate of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Zhou et al [68] applied six machine learning methods for the prediction of ROP and found that the comprehensive performance of the particle swarm optimizationextreme gradient boosting hybrid model-is superior to the other five models. Minh et al [42] used uniaxial compressive strength (UCS), Brazilian tensile strength (BTS), rock brittleness index (BI), the distance between planes of weakness (DPW) and the alpha angle (α) between the tunnel axis and the planes of weakness for predicting ROP. Minh et al [42] suggested that the fuzzy logic as well as other artificial intelligences can also be used as very good alternatives to predict ROP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al [68] applied six machine learning methods for the prediction of ROP and found that the comprehensive performance of the particle swarm optimizationextreme gradient boosting hybrid model-is superior to the other five models. Minh et al [42] used uniaxial compressive strength (UCS), Brazilian tensile strength (BTS), rock brittleness index (BI), the distance between planes of weakness (DPW) and the alpha angle (α) between the tunnel axis and the planes of weakness for predicting ROP. Minh et al [42] suggested that the fuzzy logic as well as other artificial intelligences can also be used as very good alternatives to predict ROP.…”
Section: Introductionmentioning
confidence: 99%
“…Minh et al [42] used uniaxial compressive strength (UCS), Brazilian tensile strength (BTS), rock brittleness index (BI), the distance between planes of weakness (DPW) and the alpha angle (α) between the tunnel axis and the planes of weakness for predicting ROP. Minh et al [42] suggested that the fuzzy logic as well as other artificial intelligences can also be used as very good alternatives to predict ROP. Jung et al [28] predicted the ground conditions ahead of the tunnel face regardless of site conditions considering the operational data of the shield TBM acquired during the tunnel excavation stage.…”
Section: Introductionmentioning
confidence: 99%
“…Several machine learning models have been used to predict AR by utilizing great amount of recorded data by TBM during tunnelling, including artificial neural networks (ANN) [11,12], support vector regression (SVR) [6,13], random forest (RF) [14,15], fuzzy logic [16,17], and classification and regression tress [18,19]. Among them, two models, SVR and RF, became the most widely adopted for AR prediction due to their robustness and high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In predicting FPI values, Feng et al [27] and Adoko and Yagiz [28] tried to solve this problem by proposing deep learning and FIS techniques, respectively. A group of other authors tried to solve performance of TBM using other single intelligent approaches like group modeling of data handling, genetic-based and neuro-fuzzy [2,9,[29][30][31]. On the other hand, some other scholars developed advanced intelligent techniques for this problem which are based on a combination of at least two different intelligent models [1,10,14,32,33].…”
Section: Introductionmentioning
confidence: 99%